DIGITAL TECHNOLOGIES IN VOCATIONAL EDUCATION: PROSPECTS FOR REBUILDING THE COUNTRY (Innovative professional education, 2024)
The article examines the prospects of using digital technologies in vocational education for the reconstruction of Ukraine. Particular attention is paid to the digitalisation of the educational process and its role in improving the quality of training of future professionals in the post-war period.
Keywords: digital technologies, vocational education, reconstruction, digitalization, post- war period